2022
DOI: 10.1177/14759217211061399
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and challenges in machine learning approach for structural crack assessment

Abstract: Structural health monitoring and assessment (SHMA) is exceptionally essential for preserving and sustaining any mechanical structure’s service life. A successful assessment should provide reliable and resolute information to maintain the continuous performance of the structure. This information can effectively determine crack progression and its overall impact on the structural operation. However, the available sensing techniques and methods for performing SHMA generate raw measurements that require significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…The target/outputs for the dataset are either unknown or known in unsupervised and supervised algorithms, respectively. Density estimation is typically an unsupervised problem, whereas classification and regression are supervised approaches [13]. Logistic regression, Decision tree, Support vector machine (SVM), and K-nearest neighbour (KNN) methods are used in this study for this purpose.…”
Section: Methodsmentioning
confidence: 99%
“…The target/outputs for the dataset are either unknown or known in unsupervised and supervised algorithms, respectively. Density estimation is typically an unsupervised problem, whereas classification and regression are supervised approaches [13]. Logistic regression, Decision tree, Support vector machine (SVM), and K-nearest neighbour (KNN) methods are used in this study for this purpose.…”
Section: Methodsmentioning
confidence: 99%
“…Some scholars such as [ 24 ] have examined the performance of different SVM kernels, and their results confirmed that Gaussian RBF and polynomial were the best choices for damage detection using acoustic signals. On the other hand, [ 25 ] observed that Gaussian RBF and hyperbolic tangent were the best for genome-wide prediction. Less popular kernels might achieve better findings compared to the more common kernels.…”
Section: Analysis Processmentioning
confidence: 99%
“…Deep learning techniques can often achieve a high accuracy but may require a larger amount of data and more computational resources. At this point, advanced learning strategies (e.g., Bayesian optimization) and feature extraction approaches (e.g., PCA) can be applied to reduce the time needed for training and testing machine learning algorithms [ 16 , 25 , 26 , 47 ]. The use of two- or three-layer deep neural networks (DNNs) for fatigue crack growth rate prediction could potentially be effective, depending on the complexity of the problem and the amount of data available.…”
Section: Analysis Processmentioning
confidence: 99%
“…With increasing computational capabilities, sophisticated multiscale modeling frameworks 18 and data‐driven machine learning approaches 19 have been used to study the complex phenomena behind the propagation of small cracks. Still, the data‐driven approaches face several challenges due to the limited availability of high‐quality experimental data 20 . Consequently, microstructurally small fatigue crack growth and crack interactions with the microstructure is still an open topic due to the complex three‐dimensional nature of the problem and the experimental challenges of observing the phenomena at such a small scale 21 …”
Section: Introductionmentioning
confidence: 99%
“…Still, the data-driven approaches face several challenges due to the limited availability of high-quality experimental data. 20 Consequently, microstructurally small fatigue crack growth and crack interactions with the microstructure is still an open topic due to the complex threedimensional nature of the problem and the experimental challenges of observing the phenomena at such a small scale. 21 The behavior of microstructurally small cracks is often investigated with a focus on the crack driving force.…”
Section: Introductionmentioning
confidence: 99%